ALTERNATIF MODEL PENANAMAN PENDIDIKAN KARAKTER UNTUK TINGKAT MADRASAH TSANAWIYAH MENURUT KITAB ADABUL ALIM WAL MUTA'ALLIM KARYA KH.HASYIM ARSYARI - Hidayah, Fathi; Sidon, Bey Arifin; Fahrurrozi, Agus (INCARE, International Journal of Educational Resources, 2022)
The process of character education is seen as a conscious and planned effort, not a business that happens by chance. On this basis, character education is a genuine effort to understand, shape, and foster ethical values ??both for oneself and for all members of society , especially for students as a whole. The environment that is very influential in developing character is the educational environment such as educational institutions and anything related. The concept of character education is the book Adabul Alim Wal Muta'allim by KH. Hasyim Asy'ari on the Ethics of Teachers and Students. This study aims to explain what models of character education are in the book Adabul Alim Wal Muta'allim by KH. Hasyim Asyari and alternative models of character education at the MTS level according to the book Adabul Alim Wal Muta'allim by KH. Hashim. Meanwhile , this research uses a type of library research or library research because in the context of library research the data is taken from the exploration of library materials in a holistic manner which is then analyzed based on the framework of thinking or the philosophical paradigm that underlies it.